A critical review of ozanimod for the treatment of adults with moderately to severely active ulcerative colitis. (4th May 2022) - Aoun, Roni; Hanauer, Stephen
ABSTRACT: Introduction: Ozanimod is a sphingosine-1-phosphate (S1P) modulator that inhibits lymphocyte trafficking from lymph nodes to the circulation. It is approved by the US Food and Drug Administration (FDA) for the treatment of relapsing multiple sclerosis and most recently for the management of moderate-severe ulcerative colitis (UC). Areas Covered: Here we review the status of drugs approved for moderate-severe UC, the unmet needs in the management of UC, proposed mechanisms of action of S1P modulators, clinical data regarding ozanimod in UC, and emerging S1P modulators being evaluated in inflammatory bowel disease. Expert opinion: Ozanimod is superior to placebo in inducing and maintaining clinical and endoscopic remission in UC. Adverse events include transient asymptomatic bradycardia, first-degree atrioventricular blocks, transient asymptomatic hepatotoxicity, macular edema in patients with preexisting risk factors, and increased risk of nasopharyngitis. Ozanimod is contraindicated in patients with clinically significant cardiovascular diseases, type II second-, or third-degree atrioventricular blocks, and females of childbearing age who do not use contraception. Ozanimod is the first S1P modulator to be approved for UC, offering a new therapeutic class option for patients. It has the advantages of being convenient with a once-daily oral administration, non-immunogenic, and overall safe when used in patients without contraindications.